G ATA2 mediates the negative regulation of the prepro-thyrotropin-releasing hormone gene by liganded T3 receptor β2 in the rat hypothalamic paraventricular nucleus - Kuroda, Go; Sasaki, Shigekazu; Matsushita, Akio; Ohba, Kenji; Sakai, Yuki; Shinkai, Shinsuke; Nakamura, Hiroko Misawa; Yamagishi, Satoru; Sato, Kohji; Hirahara, Naoko; Oki, Yutaka; Ito, Masahiko; et al. (PLOS ONE, 2020)
Thyroid hormone (T3) inhibits thyrotropin-releasing hormone (TRH) synthesis in the hypothalamic paraventricular nucleus (PVN). Although the T3 receptor (TR) β2 is known to mediate the negative regulation of the prepro-TRH gene, its molecular mechanism remains unknown. Our previous studies on the T3-dependent negative regulation of the thyrotropin β subunit (TSHβ) gene suggest that there is a tethering mechanism, whereby liganded TRβ2 interferes with the function of the transcription factor, GATA2, a critical activator of the TSHβ gene. Interestingly, the transcription factors Sim1 and Arnt2, the determinants of PVN differentiation in the hypothalamus, are reported to induce expression of TRβ2 and GATA2 in cultured neuronal cells. Here, we confirmed the expression of the GATA2 protein in the TRH neuron of the rat PVN using immunohistochemistry with an anti-GATA2 antibody. According to an experimental study from transgenic mice, a region of the rat prepro-TRH promoter from nt. -547 to nt. +84 was able to mediate its expression in the PVN. We constructed a chloramphenicol acetyltransferase (CAT) reporter gene containing this promoter sequence (rTRH(547)-CAT) and showed that GATA2 activated the promoter in monkey kidney-derived CV1 cells. Deletion and mutation analyses identified a functional GATA-responsive element (GATA-RE) between nt. -357 and nt. -352. When TRβ2 was co-expressed, T3 reduced GATA2-dependent promoter activity to approximately 30%. Unexpectedly, T3-dependent negative regulation was maintained after mutation of the reported negative T3-responsive element, site 4. T3 also inhibited the GATA2-dependent transcription enhanced by cAMP agonist, 8-bromo-cAMP. A rat thyroid medullary carcinoma cell line, CA77, is known to express the preproTRH mRNA. Using a chromatin immunoprecipitation assay with this cell line where GATA2 expression plasmid was transfected, we observed the recognition of the GATA-RE by GATA2. We also confirmed GATA2 binding using gel shift assay with the probe for the GATA-RE. In CA77 cells, the activity of rTRH(547)-CAT was potentiated by overexpression of GATA2, and it was inhibited in a T3-dependent manner. These results suggest that GATA2 transactivates the rat prepro-TRH gene and that liganded TRβ2 interferes with this activation via a tethering mechanism as in the case of the TSHβ gene.